Analysis of GJB2 (Connexin 26) Mutation in Patients with Congenital Non-Syndromic Sensorineural Hearing Loss - Kaskalan, Emin; Onalan, Ebru Etem; Kaygusuz, Irfan; Karlidag, Turgut; Keles, Erol; Akyigit, Abdulvahap; Yalcin, Sinasi (Galenos Yayincilik, 2014)
Objective: This study was performed to investigate the GJB2 (connexin 26) gene mutations that are the most frequent cause of sensorineural deafness in patients with congenital non-syndromic sensorineural hearing loss in our region. Methods: Sixty patients [35 males (58.3%) and 25 females (41.7%)] between the age of 2-43 years (12.11 +/- 9.03) diagnosed with congenital non-syndromic sensorineural hearing loss were included in the study. The control group consisted of 60 individuals with similar demographic features having no hearing problems. 35delG, 167delT, delE120 and 235delC of GJB2 gene mutations and GJB6 gene mutations, and the presence of new mutations were also investigated by analysis of DNA sequences in all individuals. Results: Mutations were identified in 6 (10%) of the 60 patients in the study group. Five of these (8.3% of total) had 35delG and one (1.7%) had a delE120. No mutation was detected in control group individuals. In the study group, a statistically significant correlation was determined between the presence of familial sensorineural hearing loss history and 35delG or delE120 mutation (p=0.011, p=0.034). Conclusion: This is the first study which investigated the GJB2 gene mutation in our region, and our results indicate that 35delG mutation was the most frequent. We believe that our results are noteworthy for the identification of heterozygous or homozygous individuals and the genetic counseling of patients with congenital non-syndromic sensorineural hearing loss and their family.
Keywords: Congenital hearing loss; mutation; GJB2; 35delG; 167delT